Unraveling EMI as a predictor of English proficiency in Vietnamese higher education: Exploring learners’ backgrounds as a variable - Nguyen, An (Studies in Second Language Learning and Teaching, 2023)
One key objective of English medium instruction (EMI) programs in non-Anglophone countries is to improve students’ English skills in both academic and professional environments. Despite the high cost and the popularity of the program policy, there remains a lack of empirical studies on the link between attending an EMI program and students’ English proficiency. This paper employs data from 111 students majoring in international business from a top Vietnamese university to compare English competency, measured by the Duolingo Test, between students enrolled in an EMI program and their counterparts who are taught the same curriculum but in the native language, through Vietnamese medium instruction (VMI). Controlling for different social backgrounds, the study shows that participation in EMI is associated with better English test performance. Analysis using multiple interaction terms shows that male EMI participants, or students coming from lower-income households, having lower English scores in high school, and attending more English private tutoring would benefit more from EMI. The analysis sheds light on potential socioeconomic obstacles to accessing EMI and English skill development. Follow-up interviews similarly show the relevance of demographic backgrounds to the students’ perceptions of EMI and their English proficiency. The study provides clear evidence of substantial associations between EMI and English skills. Further studies are needed to establish the causality of the results.